Mother’s Accompaniment in Exclusive Breastfeeding in Surakarta City - Ropitasari Ropitasari; Sri Anggarini Parwatiningsih; Fresthy Astrika Yunita; M.Nur Dewi Kartika; Hardiningsih Hardiningsih; Cahyaning Setyo Hutomo; Rizka Adela Fatsena; Anis Laela Megasari; Retno Tri Astuti (Global Health Science Group, 2020)
The huge benefits of exclusive breastfeeding have not been able to increase the number of exclusive breastfeeding coverage in Indonesia. This is due to the low knowledge of pregnant women on the importance of exclusive breastfeeding. Low support from families, communities and health workers, especially breastfeeding counselors, is one of the factors causing the low coverage of exclusive breastfeeding. Mothers need support from those around them for success of exclusive breastfeeding behavior. The role of health workers in health promotion is also needed so that the exclusive breastfeeding program runs optimally. This activity aims to increase the knowledge and skills of mothers in exclusive breastfeeding. The community service method used is assistance to mothers in exclusive breastfeeding with the concept of one student one client. It was carried out in the working area of the Surakarta City Health Office with 30 participants. It begins with counseling mothers about exclusive breastfeeding, observations about maternal assistance in exclusive breastfeeding, and an evaluation of the course of mentoring through filling out a questionnaire about exclusive breastfeeding and breastfeeding practices. The role of health workers in supported exclusive breastfeeding includes providing counseling on IMD and breastfeeding since pregnancy with husband, involving husbands in IMD implementation, posyandu with home visits involving cadres and providing counseling for pregnant women, providing lactation corners, counseling involving all puskesmas officers, distributing leaflets and posters, holding pregnancy classes, and involving cadresto hold Kelompok Pendukung Ibu (KP-Ibu). The failure of exclusive breastfeeding was generally because the mother works so that breastfeeding motivation decreased, family support was low, worried about insufficient breastfeeding, and low knowledge of breastfeeding. There was a relationship between knowledge and breastfeeding practice and it was statistically significant (p=0.004, OR: 25.14, CI95%:0.89-5.56). The role of health workers and cadres in supported exclusive breastfeeding through maternal assistance was quite good, however the failure of exclusive breastfeeding generally came from maternal factors. There was a relationship between knowledge and breastfeeding practice and statistically significant.